Final results of the CUPID-0 Phase I experiment. (February 2020) - Casali, N; Azzolini, O; Beeman, J W; Bellini, F; Beretta, M; Biassoni, M; Brofferio, C; Bucci, C; Capelli, S; Cardani, L; Carniti, P; Chiesa, D; et al.
Abstract: A convincing observation of neutrino-less double beta decay (0 v DBD) relies on the possibility of operating high-energy resolution detectors in background-free conditions. Scintillating cryogenic calorimeters are one of the most promising tools to fulfill the requirements for a next-generation experiment. Several steps have been taken to demonstrate the maturity of this technique, starting form the successful experience of CUPID-0. The CUPID-0 experiment collected almost 10 kg y of exposure, running 26 Zn 82 Se crystals during two years of continuous detector operation. The complete rejection of the dominant α background was demonstrated, measuring the lowest counting rate in the region of interest for this technique. Furthermore, the most stringent limit on the 82 Se 0 v DBD was established. In this contribution we present the final results of CUPID-0 phase-I, including a detailed model of the background and the measurement of the 2 v DBD half-life.